Preferential adsorption of Cd, Cs and Zn onto virgin polyethylene microplastic versus sediment particles. (July 2020) - Besson, Marc; Jacob, Hugo; Oberhaensli, François; Taylor, Angus; Swarzenski, Peter W.; Metian, Marc
Abstract: Plastic pollution has become a major environmental concern worldwide, and marine ecosystems have become polluted with ubiquitous microplastic particles (MP). MP can contain chemical additives and can also scavenge pollutants from the surrounding environment, and these co-contaminants may threaten the marine biota when MP become inadvertently ingested and transferred up the food chain. However, our understanding of the sorption-desorption kinetics of chemical compounds bound to MP remains limited. Moreover, whether MP are better transport vectors of co-contaminants than other natural particles (e.g. sediment) has not received much attention. Here, we used radiotracers to examine the partition coefficients ( K d ) of three trace metals ( 109 Cd, 134 Cs, and 65 Zn) to virgin MP (32–75 μm polyethylene beads) and to natural sediment particles of a similar size (35–91 μm) in seawater. After 72 h, sediment particles adsorbed 2.5% of 109 Cd, 68.0% of 134 Cs, and 71.0% of 65 Zn, while MP adsorbed <0.8% of these three elements. Results highlight that under these experimental conditions, virgin polyethylene MP may not be effective transport vectors for these trace metals. Important variations in K d were observed between elements, inciting for further studies to decipher how chemical characteristics, MP composition, and associated-biofilms, all interact in these biokinetic processes. These results demonstrate how radiotracers can allow us to address important knowledge gaps and broaden our understanding regarding the interactions between waterborne contaminants, naturally occurring particles and marine wildlife.